2018
DOI: 10.1002/joc.5415
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear response of precipitation to climate indices using a non‐stationary Poisson‐generalized Pareto model: case study of southeastern Canada

Abstract: Quantile estimates are generally interpreted in association with the return period concept in practical engineering. To do so with the peaks‐over‐threshold (POT) approach, combined Poisson‐generalized Pareto distributions (referred to as PD‐GPD model) must be considered. In this article, we evaluate the incorporation of non‐stationarity in the generalized Pareto distribution (GPD) and the Poisson distribution (PD) using, respectively, the smoothing‐based B‐spline functions and the logarithmic link function. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Therefore, it is necessary to develop research that helps to understand how these events behave over time, in addition to predicting the probability of occurrence of a specific event at regular intervals of time. In this respect, extreme value theory (EVT) has often been used to model extreme weather events for both global studies (Serinaldi and Kilsby, 2014) and regional studies, such as in Canada (Thiombiano et al, 2018), Finland (Pedretti and Irannezhad, 2018), China (Tu et al, 2017;Mo et al, 2018), Portugal (Santos et al, 2017a), Jakarta (Siswanto et al, 2016), Vietnam (Gobin et al, 2016), Korea (Chen et al, 2016), and United States (Heaton et al, 2011). In Brazil, EVT has been used to characterize the distribution of rainfall extremes in the city of São Paulo (Sugahara et al, 2008), the Amazon Basin (Santos et al, 2015(Santos et al, , 2016 and the city of Curitiba (Pedron et al, 2016).…”
mentioning
confidence: 99%
“…Therefore, it is necessary to develop research that helps to understand how these events behave over time, in addition to predicting the probability of occurrence of a specific event at regular intervals of time. In this respect, extreme value theory (EVT) has often been used to model extreme weather events for both global studies (Serinaldi and Kilsby, 2014) and regional studies, such as in Canada (Thiombiano et al, 2018), Finland (Pedretti and Irannezhad, 2018), China (Tu et al, 2017;Mo et al, 2018), Portugal (Santos et al, 2017a), Jakarta (Siswanto et al, 2016), Vietnam (Gobin et al, 2016), Korea (Chen et al, 2016), and United States (Heaton et al, 2011). In Brazil, EVT has been used to characterize the distribution of rainfall extremes in the city of São Paulo (Sugahara et al, 2008), the Amazon Basin (Santos et al, 2015(Santos et al, , 2016 and the city of Curitiba (Pedron et al, 2016).…”
mentioning
confidence: 99%
“…They found that rainfall extremes could exhibit notable departures from independence, which could have important implications on POT based FFA under both stationary and non-stationary regimes. Thiombiano et al (2017) and Thiombiano et al (2018) presented how climate change indices can be used as covariates in a non-stationary framework in the POT modelling.…”
Section: Stationaritymentioning
confidence: 99%
“…In addition, it reduces the analytical and computational burden of uncertainty assessment by narrowing down the number of model candidates. Even if several exogenous variables are used as covariates for nonstationary extreme value modeling, a number of candidate models can be considered due to probability distribution types [19], combinations of covariates [8,9], and their link function types [26,31,33]. Therefore, our suggested model selection procedure can be an efficient and reasonable way to select the most appropriate model.…”
Section: Consideration Of Uncertainty In Model Selectionmentioning
confidence: 99%
“…The use of a more complex model (i.e., nonstationary distribution model) generally allows a good fit for the given samples, but this could provide quantile estimates with a large amount of uncertainty [3]. In general, however, the best model is selected using only the information criteria that assess the model performance based on the maximized log-likelihood (i.e., model fit) [26,[28][29][30][31][32][33], so that the selected nonstationary model usually yields unreliable design quantiles [16]. Cooley [34] demonstrated that relying solely on the information criteria is not enough to select an appropriate model because they cannot take into account uncertainty.…”
Section: Introductionmentioning
confidence: 99%